Role of transabdominal Ultrasonography in the evaluation of suspected ectopic pregnancy - Nahar, Mst Nazmun; Sattar, Asifa; Ara, Husne; Rabbi, Akanda Fazle; Shirin, Mahbuba; Kumu, Farhana Kamal (Journal of Dhaka Medical College, 2015)
The study was carried out to assess the diagnostic accuracy of transabdominal ultrasonography in the evaluation of clinically suspected ectopic pregnancy patients . This cross sectional study was carried out in the department of Radiology and Imaging, Dhaka Medical College Hospital, Dhaka, from July 2006 to June 2008. 50 patients were selected purposively and transabdominal ultrasonography was done in each patient by 3.5 MHz frequency curvilinearprobe. Findings of transabdominal ultrasonography were then compared with the peroperative findings. Transabdominal ultrasonography in the diagnosis of ectopic pregnancy showed a sensitivity of 79.5%, specificity of 83.3%, and accuracy of 80%. Positive predictive value was 97.2% and negativepredictive value was 55.6%. . This study shows thattransabdominal ultrasonographyis an effective modality in the evaluation of ectopic pregnancy and should be used as a routine first-step procedure in patients of suspected ectopic pregnancy. DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21529 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 167-172